Finding your career in the modern audio industry - Tucker, April (Routledge, 2022)
"Finding Your Career in the Modern Audio Industry equips the reader with the skills they need to turn an interest in audio, sound, or music technology into a career. This book provides insight for aspiring professionals seeking audio-related opportunities in entertainment, technology, education, and more. In the audio industry, there is typically a gap between those in-training and those with professional (and financially sustainable) careers. This book bridges the information gap, offering practical and real-world advice to those in this volatile stage of their career. Including 70+ interviews with professionals from over 20 countries, Finding Your Career in the Modern Audio Industry offers insight into how others (across the industry and the world) have applied entrepreneurial thinking, problem-solving, and creative solutions to build their careers. Including international case studies and interviews with diverse professionals, Finding Your Career in the Modern Audio Industry is essential reading for anyone taking their first steps into an audio-related field"--